Epidemiological Characteristics, Disease Knowledge of COVID-19 Patients in Dong Thap - Duy Anh, Dao; Tuan Son, Nguyen; Thi Nhung, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 3, 2022)
Abstract: A cross-sectional descriptive study was conducted from August 2021 to September 2021 to describe the epidemiological characteristics of COVID-19 patients at the field hospital in Dong Thap Community College. The study collected epidemiological data from 240 subjects. The results show that the male/female ratio is 1.2/1; the mean age was 29.2±15.1(1-65) years old; the proportion of subjects having contact with the pandemic area is 90%. The percentage of patients who caught Covid-19 from their family is the highest (62.1%), followed by the number of patients with an unknown source of infection (24.6%) and the number of patients who caught Covid-19 from community transmission (13.3%). The mean time between infection to hospitalization was 4.8 days. The percentage of subjects having 1 st dose of vaccine is 12.5%. Most patients acknowledge the COVID-19 pandemic and know the modes of transmission of the SARS-CoV-2 virus. Most of the sick people practiced adequately or inadequately 5K measures in the community and did not practice disease prevention measures at home. The goals of this study are: i) Contributing to a general assessment of epidemiological factors and the accumulated understanding of the disease of COVID-19 patients in general, and COVID-19 subjects at the field hospital of Dong Thap Community College in particular; and ii) Contributing to the development of better disease prevention measures. Keywords: COVID-19, SARS-CoV-2, epidemiological characteristics.